Efisiensi Wakaf Tunai Dalam Meningkatkan Keuangan Dan Perbankan Syariah - Ani Faujiah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Waqf has long been known by the Muslim community as a form of charity that plays an important role in social, economic and cultural development in order to improve the welfare of the community. One form of waqf that has recently been introduced is cash waqf. Cash waqf as an alternative to poverty alleviation has been implemented in several Islamic countries. In Bangladesh waqf has been managed by Social Investment Bank Ltd (SIBL) which has developed a social capital market in the voluntary sector, cash waqf opens unique opportunities for investment creation in the fields of religion, education and social services. This research is a qualitative research that is literature review. The approach used is descriptive critical analysis. Types and sources of data are secondary data obtained from research results, articles and reference books that discuss the same topic. Waqf is a muamalah activity that has spiritual, social and economic dimensions. Traditionally, so far, waqf has only been interpreted as a gift in the form of immovable property such as land and buildings whose purpose is limited to the construction of houses of worship and education. However, in fact waqf of movable goods such as cash waqf (money) has long been practiced by Muslims such as during the Umayyad and Abbasid dynasties, only not as popular as land or building waqf. Currently, along with the development of public understanding of Islamic philanthropic practices, waqf especially cash waqf is directed towards economic development and empowerment,